Impact of Employees’ Perceptions of Organizational Downsizing Practices on Their Commitment - M. D. K. Erandika; V. R. Ranasinghe (Kelaniya Journal of Management)
Sri Lanka is presently facing with its most severe financial crisis in decades, with the building and construction sector being significantly affected. This study aims to investigate whether employees’ perceptions of organizational downsizing practices influence their commitment. It was conducted as a cross-sectional study among a sample of 204 employees from three downsized construction firms in the Colombo District. The sample was selected using a simple random sampling technique, and data were collected through the distribution of an online standard questionnaire. The data were analyzed using SPSS version 23.0, employing descriptive statistics, correlation, and simple regression. The analysis revealed that employees’ perceptions of their organizations’ downsizing practices have a significant positive impact on their levels of affective, continuance, and normative commitment. Effective communication throughout the downsizing process, including before, during, and after, is recommended as a means to mitigate the adverse effects of downsizing on employee commitment.